The Transcription Factor NF-κB and the Regulation of Vascular Cell Function - Rainer de Martin; Martina Hoeth; Renate Hofer-Warbinek; Johannes A. Schmid (2000)
Abstract —A variety of pathophysiological situations that affect cells of the vasculature, including endothelial and smooth muscle cells, leads to the expression of genes such as adhesion molecules and chemokines that are dependent on members of the nuclear factor (NF)-κB family of transcription factors. The corresponding gene products mediate important biological functions such as immune and inflammatory reactions, smooth muscle cell proliferation, and angiogenesis. The beneficial and usually transient NF-κB–dependent gene expression may be exaggerated in pathological situations and results in damage to the vessel wall and impaired vascular cell function. In this review, we will capitalize on the favorable and adverse roles of NF-κB in the context of vascular disease, eg, chronic and localized inflammation, arteriosclerosis, and neoangiogenesis.